Komponen Asam Amino dan Aktivitas Enzim Tripsin dari Usus Tuna Sirip Kuning (Thunnus albacares) dan Kakap Merah (Lutjanus campechanus): Amino Acid Components and Trypsin Enzyme Activity from Intestines of Yellowfin Tuna (Thunnus albacares, Bonnaterre 1788) and Red Snapper (Lutjanus campechanus, Poey 1860) - Arbajayanti, Rahma Dini; Nurhayati, Tati; Nurilmala, Mala (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
Fish entrails is known as a source of digestive enzymes, especially proteinases such as trypsin. Trypsin characteristics are affected by fish species and habitat.. The aim of this study was to compare the amino acid component of meat and the activity of trypsin crude extract from intestinal of yellowfin tuna (Thunnus albacares) and red snapper (Lutjanus campechanus). The fish morphometric and the ratio of the fish entrail were observed. Furthermore and , the chemical composition, amino acid components of the meat and trypsin crude extract activity were analyzed.. In general, yellowfin tuna has a higher amino acid composition than red snapper, especially in the amino acid components histidine, leucine, aspartic acid, lysine and glutamic acid. The most dominant amino acid component found in the two fish is glutamic acid. The trypsin crude extract from tuna intestines had a higher activity (4.908 U/mg) compared to that from snapper intestines (4.908 vs 0.076 U/mg).